UPAYA MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS VII-J SMP NEGERI 4 MADIUN MELALUI MODEL PEMBELAJARAN INKUIRI - Wiyola Nensiana Sari; Gregoria Ariyanti (Universitas Katolik Widya Mandala Surabaya Kampus Kota Madiun, 2016)
The aim of learning ideally is to lead the student in comprehending the given materials. In terms of students` capabilities, the students nowadays tend to have a very low capability which is actually caused by their lack of knowledge in problem solving. Hence, this is supported by their dependency to their teacher in doing the exercises. In other words, they cannot do their exercises without their teacher`s help. Besides, the way how the teacher limits the student`s creativity in comprehending such an exercise is considered as one of factors that decrease the students` critical review. Therefore, it needs a certain model that stimulates student to observe a particular knowledge in learning. Thus, the appropriate model in this case is inquiry model. This research is intended to increase the students` critical review by applying inquiry model. Furthermore, Classroom Action Research (CAR) is applied in this research. Moreover, this kind of research is materialized by two cycles. Furthermore, CAR consists of observing, planning and evaluating. The subject of the research is the student of VII-J (first grade of Junior High School) of SMPN 4 Madiun. The total population is 30 students. The analysis is presented as the following : 1. The average score test in Cycle I is 67,5, Cycle II : 83,34. Moreover, the class completion rate in cycle I is 56,66%, Cycle II : 82,75%. This proves that the students` critical review in writing is increased.2. The average score test through the learning activity in Cycle I is 3,1225. In this case, the cycle I is classified as a good category. While the cycle II the total score reaches 3,435. In this case, the cycle II is classified as an excellent category. The result shows that the teacher`s ability in applying inquiry model learning is improved.3. The inquiry model learning is considered as the best way to increase the students` critical review. Key word : Students` Critical Review, inquiry model learning